Identification and Gene Fine Mapping of the Bisexual Sterility Mutant Meiosis Abnormal Bisexual Sterility 1 in Rice - Yingchun Wan; Xiaoqing Liu; Nan Wang; Zhengming Zeng; Yudong Jiang (Current Issues in Molecular Biology, 2024)
Exploring the genes regulating rice fertility is of great value for studying the molecular mechanisms of rice reproductive development and production practices. In this study, we identified a sterile mutant from the mutant library induced by ethyl methanesulfonate (EMS), designated as meiosis abnormal bisexual sterility 1 (mabs1). The mabs1 mutant exhibits no phenotypic differences from the wild-type during the vegetative growth phase but shows complete sterility during the reproductive growth phase. Phenotypic observations revealed that both pollen and embryo sac fertility are lost in mabs1. Notably, in mabs1, the development of the anther inner and outer walls, tapetum degeneration, and callose synthesis and degradation all proceed normally, yet meiosis fails to form normal tetrads. Genetic analysis indicated that this mutant trait is controlled by a single recessive nuclear gene. By constructing a genetic segregation population, we successfully mapped the MABS1 gene to a 49 kb region between primer markers Y7 and Y9 on chromosome 1. Resequencing revealed a single-nucleotide substitution in the exon of the LOC_Os01g66170 gene, which resulted in a change from Valine to Isoleucine. Subsequent sequencing of this locus in both wild-type and mabs1 mutants confirmed this mutation. Therefore, we have identified the gene at LOC_Os01g66170 as a candidate for MABS1, a previously unreported novel gene involved in rice meiosis. Through RT-qPCR, we found that the expression levels of multiple meiosis-related genes were significantly changed in the mabs1 mutant. Therefore, we believe that MABS1 is also involved in the process of rice meiosis. This study lays the groundwork for a functional study of MABS1.